Treatment outcome of diffuse large B-cell lymphoma involving the head and neck: Two-institutional study for the significance of radiotherapy after R-CHOP chemotherapy - Kwak, Yoo-Kang (Medicine (Baltimore), 2017)
This study was performed to analyze the treatment outcome for diffuse large B-cell lymphoma (DLBCL) involving the head and neck and to evaluate the role of radiotherapy in the rituximab era. Fifty-six patients diagnosed with DLBCL involving the head and neck were assessed. All patients were treated with 6 cycles of rituximab, cyclophosphamide, adriamycin, vincristine, and prednisolone (R-CHOP). After chemotherapy, radiation was delivered to the head and neck area in a median dose of 36 Gy. Radiation was delivered using 3-dimensional radiotherapy (n  =  25) or intensity-modulated radiotherapy (n  =  31). Primary endpoints were relapse-free survival (RFS), overall survival (OS), and local control rate. After median follow-up time of 45 months, the 5-year RFS and OS rates were 72% and 61%, respectively. Fourteen (25%) of 56 patients relapsed; 1 had a local relapse, 11 had distant relapses, and 2 had both local and distant relapses. The final local control rate after radiotherapy was 94%. Age, performance status, international prognostic index score, and radiotherapy response were significant prognostic factors for both RFS and OS in the multivariate analysis. Incidence of acute grade 3 and 4 hematologic toxicity was 9% and 4%, respectively. Grade 3 nonhematologic toxicity occurred in 2 (4%) patients, and there was no grade 4 nonhematologic toxicity for the irradiated patients. Excellent local control and survival rates can be achieved with R-CHOP followed by radiotherapy in patients with DLBCL involving the head and neck. Treatment-related toxicity after the introduction of modern radiotherapy was acceptable and limited.